On Hadamard Product of Hypercomplex Numbers - Daşdemir, A. (Bulletin of the Karaganda University. Mathematics Series, 2021)
Certain product rules take various forms in the set of hypercomplex numbers. In this paper, we introduce a new multiplication form of the hypercomplex numbers that will be called «the Hadamard product», inspired by the analogous product in the real matrix space, and investigate some algebraic properties of that, including the norm of inequality. In particular, we extend our new definition and its applications to the complex matrix theory.